Regulation of strength and ductility of single-phase twinning-induced plasticity high-entropy alloys - Wei, Daixiu; Gong, Wu; Kawasaki, Takuro; Harjo, Stefanus; Kato, Hidemi (Scripta materialia, 2022)
Near-equiatomic single-phase twining-induced plasticity (TWIP) high-entropy alloys (HEAs) exhibit a good combination of strength and ductility, but their modest yield strength requires further improvement. Here, we propose a strategy for markedly enhancing their strength while retaining satisfactory ductility, taking advantage of the temperature dependence of the stacking fault energy. The room-temperature strength of a representative TWIP HEA was improved by the cryogenic pre-deformation-induced dislocations, martensite, nanotwins, and stacking faults. The tensile properties were further tuned by subsequent annealing to obtain partially recovered or recrystallized microstructures. The influence of regulated microstructures on the yield strength was clarified by neutron diffraction line profile analysis. The room temperature tensile yield strength of the HEA increased from 275 to 1012 MPa while retaining an elongation of 21.9%. The yield strength and elongation were then further altered to 826.9 MPa and 42.6%. This study presents possibilities for fabricating advanced HEAs by tuning the substructures. [Display omitted]